2015
DOI: 10.1016/j.ijgo.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Ending preventable newborn deaths in a generation

Abstract: The end of the Millennium Development Goal (MDG) era was marked in 2015, and while maternal and child mortality have been halved, MGD 4 and MDG 5 are off-track at the global level. Reductions in neonatal death rates (age <1 month) lag behind those for post-neonates (age 1-59 months), and stillbirth rates (omitted from the MDGs) have been virtually unchanged. Hence, almost half of under-five deaths are newborns, yet about 80% of these are preventable using cost-effective interventions. The Every Newborn Action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 9 publications
1
46
0
5
Order By: Relevance
“…When we used the Global Network Cause of Death algorithm to analyse data from this population‐based community study, we found that the distribution of the causes of neonatal death was similar to that reported in the literature for the four main causes .…”
Section: Discussionsupporting
confidence: 69%
“…When we used the Global Network Cause of Death algorithm to analyse data from this population‐based community study, we found that the distribution of the causes of neonatal death was similar to that reported in the literature for the four main causes .…”
Section: Discussionsupporting
confidence: 69%
“…Although both the under‐five and neonatal mortality rates dropped substantially, newborn deaths decreased at a slower rate and the proportion of under‐five deaths that occurred during the newborn period rose from 27 to 47% during this period . To address the relatively high neonatal mortality rate, and work towards ending preventable deaths by 2035 , there is a need for Ethiopia to implement effective interventions and strategies targeting newborn survival.…”
Section: Introductionmentioning
confidence: 99%
“…The resuscitation and immediate newborn care packages have been estimated to be the most effective at reducing childhood mortality [20] (Table 1). Some estimates indicate that as many as over a million lives per year could be saved with these programs [21,22]. Furthermore, packages of interventions for: (1) the detection and management of severe childhood illnesses such as diarrhea, pneumonia, meningitis and malaria, (2) improvement in nutrition, and (3) vaccination could be as effective in selective settings.…”
Section: Packages Of Interventions To Decrease Childhood Mortalitymentioning
confidence: 99%